Use of Virtualization Technology for Linux Firewall Implementation in Teaching Computer Network - Ariyanto, Yuri; Harijanto, Budi; Watequlis S., Yan; Setiawan, Awan; Rohadi, Erfan (International Journal of Engineering and Technology, 2018)
This paper describes the use of virtualization technology in the linux network teaching process in linux firewall implementation. The problem that is often faced by teacher and student is the limitation of computer devices in implementing network topology design. The use of virtualization technology can be used as a device to create a virtual network laboratory, which is an implementation of real laboratories and network simulation software that is useful to explain the concept of computer network management. With this in mind, it can provide an overview of project characteristics, especially the implementation of linux networks in the area of virtualization technology. Linux network virtualization implementation to help the teaching process used netkit. Netkit can be used as a linux network simulation, where each virtual machine host has a linux operating system, and can implement a computer network based on the design of a real network topology. The method used to implement the Linux firewall by creating a virtual laboratory, where virtual laboratories are built based on the real network topology design. Testing is done on a virtual laboratory by implementing a network topology design and running based on a test scenario.Â